2008
DOI: 10.1016/j.ajhg.2008.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in HOXA2 Is Responsible for Autosomal-Recessive Microtia in an Iranian Family

Abstract: Microtia, a congenital deformity manifesting as an abnormally shaped or absent external ear, occurs in one out of 8,000-10,000 births. We ascertained a consanguineous Iranian family segregating with autosomal-recessive bilateral microtia, mixed symmetrical severe to profound hearing impairment, and partial cleft palate. Genome-wide linkage analysis localized the responsible gene to chromosome 7p14.3-p15.3 with a maximum multi-point LOD score of 4.17. In this region, homeobox genes from the HOXA cluster were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 59 publications
3
56
0
1
Order By: Relevance
“…65,66 Homeobox A2 ( HOXA2 ) mutations have been implicated in autosomal dominant and recessive forms of microtia and hearing impairment, sometimes accompanying cleft palate. 67,68 In this study, the variant identified in HOXA2 was novel.…”
Section: Discussionmentioning
confidence: 68%
“…65,66 Homeobox A2 ( HOXA2 ) mutations have been implicated in autosomal dominant and recessive forms of microtia and hearing impairment, sometimes accompanying cleft palate. 67,68 In this study, the variant identified in HOXA2 was novel.…”
Section: Discussionmentioning
confidence: 68%
“…Whereas HOXA2 did not score very high compared to other members of the HOXA cluster in our prioritization analysis, it plays a critical role in development of the middle and external ear (Alasti et al 2008; O’Gorman 2005; Tischfield et al 2005; VieilleGrosjean et al 1997) and mutation of its highly conserved homeodomain has been causally implicated in autosomal recessive bilateral microtia, mixed symmetrical severe-to-profound hearing impairment and cleft palate (Alasti et al 2008). Of the other HOXA family members, a homozygous mutation of HOXA1 has been reported to disrupt the inner and outer ear and cause facial, brainstem and cardiac abnormalities (Tischfield et al 2005).…”
Section: Discussionmentioning
confidence: 75%
“…Hoxa2 is known to be important for anterior posterior patterning for both the hindbrain and second arch NCC (Gendron-Maguire et al, 1993; Rijli et al, 1993). Mutation of HOXA2 in humans can impact development of the inner ear (Alasti et al, 2008), but, again, the effect is unlikely to be mediated by the hindbrain (Bok et al, 2005). Because mutation of Hoxa2 causes significant mis-patterning of R4 NCC it is possible that abnormal anterior-posterior specification of the NCC could be responsible for human HOXA2 inner ear defects.…”
Section: Discussionmentioning
confidence: 99%